THE EFFECT OF DIETARY VITAMIN -C- ON THE SEVERITY OF EXPERIMENETAL INFECTIOUS BURSAL DISEASE IN BROILERS - N. AL- Taweel , R. (The Iraqi Journal of Veterinary Medicine, 1994)
Fourty chicks were used to study the effect of adding vitamin -C- to the feed on experimental infection with Infectious Bursal Disease (IBD) virus. They were devided randomly into three group. Chicks in group two received 300 mg vitamin C/Kg of food one day befor infection. Chicks in group two and three were infected by giving tissues taken from naturally infected chickens while chicks in group one served as uninfected untreated controls. The number of infected chicks were zero, 2 and 6 in group one, two and three respectively. Vitamin -C- leveles were reduced from 29.5 to 17.5 mg/100 g. of liver tissues but it rose to 19.3 in infected chickens when vitamin -C- was added. in response to stress of infection heterophils/ lymphocytes ratios was elevated form 0.5 to 0.9 but it reached 0.5 when vitamin -C- was added. The results of this experiment indecated that the severity of IBD can be reduced by adding 300 mg/Kg of vitamin -C- to the feed of broiler chicks.